2013
DOI: 10.1111/1365-2656.12121
|View full text |Cite
|
Sign up to set email alerts
|

Snake co‐occurrence patterns are best explained by habitat and hypothesized effects of interspecific interactions

Abstract: Summary1. Snakes often occur in species-rich assemblages, and sympatry is thought to be facilitated primarily by low diet overlap, not interspecific interactions. 2. We selected, a priori, three species pairs consisting of species that are morphologically and taxonomically similar and may therefore be likely to engage in interspecific, consumptive competition. We then examined a large-scale database of snake detection/nondetection data and used occupancy modelling to determine whether these species occur toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 71 publications
1
43
1
Order By: Relevance
“…Sympatric species may face exclusion, avoidance [4], or even extinction [5] because of competitive interactions, which are usually stronger between species that share similar ecological niches [6]. Therefore, mechanisms that decrease niche overlap usually help similar species persist in sympatry [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympatric species may face exclusion, avoidance [4], or even extinction [5] because of competitive interactions, which are usually stronger between species that share similar ecological niches [6]. Therefore, mechanisms that decrease niche overlap usually help similar species persist in sympatry [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, not dealing with false absences of species (i.e., non-detections) also can result in erroneous interpretations about species interaction, because these can result in biased estimation of species co-occurrence and interaction frequency [4, 14, 15]. Therefore, a framework that permits analysis of species interaction while dealing with imperfect detection and incorporating habitat characteristics directly into the modeling is more likely to result in accurate estimates of species co-occurrence [4, 14, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Past interspecific interactions may have played a role in snake co-evolution and evolutionary divergence[92,93], and habitat partition modeling has been applied to evaluate interspecific interactions that help explain occupancy patterns between sympatric snakes[93][94][95]. However, models, per se, do not rule out alternative interpretations [96] and thus a judicious hypothesis requires integrating ecological and evolutionary constraints.In this respect, molecular evidence gathered by omic technologies is increasingly used to address a wide range of evolutionary questions[97].…”
mentioning
confidence: 99%
“…Studies have demonstrated that the competition between congeneric species is intense due to the sharing of habitat and resources (Darwin 1872, Losos 1994, Steen et al 2014. Thus, different strategies emerge from phylogenetically close species to decrease competition and favor cooccurrence in a specifi c habitat (Pianka 1973).…”
Section: Introductionmentioning
confidence: 99%